2004
DOI: 10.7326/0003-4819-141-9-200411020-00011
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis: Angiotensin-Receptor Blockers in Chronic Heart Failure and High-Risk Acute Myocardial Infarction

Abstract: Because ACE inhibitors and ARBs do not differ in efficacy for reducing all-cause mortality and heart failure hospitalizations in patients with chronic heart failure and in patients with high-risk acute MI, ARBs should be regarded as suitable alternatives to ACE inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(104 citation statements)
references
References 46 publications
5
95
1
3
Order By: Relevance
“…ELITE II [7], the largest study to date comparing ACE inhibitors and ARBs in CHF using mortality as the primary endpoint, found that the two classes of drugs were similar in their reduction of mortality (hazard ratio comparing losartan to captopril 1.13, 95% confidence interval 0.95, 1.35). The findings of ELITE II were recently confirmed in a large meta-analysis comparing ARBs to ACE inhibitors (odds ratio for all-cause mortality 1.06, 95% confidence interval 0.90, 1.26) [6]. Similarly, two studies comparing an ARB to an ACE inhibitor after acute myocardial infarction failed to show superiority of the ARB.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…ELITE II [7], the largest study to date comparing ACE inhibitors and ARBs in CHF using mortality as the primary endpoint, found that the two classes of drugs were similar in their reduction of mortality (hazard ratio comparing losartan to captopril 1.13, 95% confidence interval 0.95, 1.35). The findings of ELITE II were recently confirmed in a large meta-analysis comparing ARBs to ACE inhibitors (odds ratio for all-cause mortality 1.06, 95% confidence interval 0.90, 1.26) [6]. Similarly, two studies comparing an ARB to an ACE inhibitor after acute myocardial infarction failed to show superiority of the ARB.…”
Section: Discussionmentioning
confidence: 85%
“…Several large clinical trials have clearly shown that ACE inhibitors [5] and angiotensin receptor blockers (ARBs) [6] improve survival in patients with CHF compared to placebo. In a head-to-head comparison, the improvement in survival in patients with CHF was comparable between losartan, an ARB, and captopril, an ACE inhibitor [7].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, randomized controlled trials (RCTs) have reported an increased risk of renal dysfunction among patients given combination therapy compared with patients given an ACE inhibitor or an angiotensinreceptor blocker alone (i.e., monotherapy). [4][5][6][7][8] It is not known whether the absolute risks of adverse renal outcomes would be the same in clinical practice as they are in RCTs.…”
mentioning
confidence: 99%
“…In a recent meta-analysis, comparison of an ACE inhibitor and an angiotensin II receptor blockers in conditions of impaired cardiac function such as heart failure and postmyocardial infarction has not shown significant differences. 31 No difference in clinical outcomes has also been reported in other meta-analyses, 32,33 including the one that taking into account 25 trials involving a total of 68 711 patients at risk for coronary events, which showed that the odds ratio for a myocardial infarction associated with an angiotensin II receptor blockers was 1.03. 32 Nevertheless, another metaanalysis has reported that angiotensin II receptor blockers, which are beneficial on stroke and heart failure outcomes, may be less effective with regard to myocardial infarction.…”
Section: Angiotensin II Receptor Blockers Versus Ace Inhibitors On Hamentioning
confidence: 89%